Comparison of RPE at ventilatory and at 60% of VO2max on six different exercise modes - Ziogas, G.; Thomas, T. R.; Smith, T. D.; Zhang, Q.; Londeree, B. R. (Medicine & Science in Sports & Exercise, 1994)
RPE is correlated to, but not causally related to, end exercise VO2, VE, HR, HLa, GLU, EPI, and NE. Implication: RPE is the best indicator of exercise response.